Rare GCC2-ALK fusion G13:A20 detected by next generation sequencing in non-small cell lung cancer patients and treatment response - Qin, Jing; Zeng, Daxiong; Xie, Fajun; Yu, Ruoying; Wu, Xue; Liu, Kaihua; Shao, Yang W.; Lu, Hongyang; Jiang, Junhong (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Two patients with rare GCC2-ALK fusion G13:A20 which were found in Chinese population by next generation sequencing (NGS) developed resistant to crizotinib with a prolonged progression-free survival (PFS). Both patients showed unfavorable response to subsequent second or third generation tyrosine kinase inhibitors (TKIs) treatment with shorten PFS. In conclusion, non-small cell lung cancer (NSCLC) patients with rare GCC2-ALK fusion G13:A20 may be optimal candidates for crizotinib as front-line therapy and may have a high possibility to exhibit unsatisfactory response to subsequent second or third generation TKIs target therapy after acquiring resistance to crizotinib.